Desenvolvimento de um condensador cascata de CO2 e R-404A - Costa, Luciano César (My University, 2020)
In a simple cascade subcritical refrigeration system, working with CO2 as a refrigerant fluid in the low-pressure side with direct expansion, it?s necessary a heat exchanger to do the condensation. This condenser, of shell and tube type with a dual pass inside the tubes and a single pass in the shell side, that do the condensation and subcooling of the superheated R-744 (CO2) that flows inside the tubes using the energy ceded to the refrigeration fluid R-404A, this one, evaporating in the shell side. This work had, as an objective, determinate de equipment?s global heat transfer coefficient, through an ideal constructive way based in the TEMA (Tubular Exchanger Manufacturers Association) norm, for the R-404A to do the physical state change of carbon dioxide through the heat transfer. To reach the goal set, it was used the methodology in the pertinent bibliographic and grounded research, through specified calculations. The study presentation is made by the mathematic development, using Palen correlations for the shell side and inside tubes, the correlations described by Gnielinski and Iqbal and Bansal (2011). The resulting equipment had an overall heat transfer coefficient of 431 W/m²·K, with a surface heat exchange of 5.49 m², sufficient to realize the heat exchange of 28.25 kW. The results are compared to the used bibliography and the plate heat exchanger, this one showing to be more compact, although more fragile and with a higher pressure drop (sic).
Em um sistema de refrigeração subcrítico de cascata simples, que utiliza o CO2 como fluido refrigerante no lado de baixa pressão operando por expansão direta, é necessário um trocador de calor para realizar a condensação. Esse condensador, do tipo casco e tubo de dois passes nos tubos e um passe no casco, que condensa e subresfria o R-744 (CO2) superaquecido no interior dos tubos à custa da energia cedida ao fluido refrigerante R-404A, o qual evapora no lado do casco. O presente estudo teve por objetivo, determinar o coeficiente global de transferência de calor do equipamento, por meio de uma forma construtiva ideal baseada na norma TEMA (Tubular Exchanger Manufacturers Association), para que o R-404A execute a mudança de estado físico do dióxido de carbono pela transferência de calor. Para atingir a meta traçada foi utilizada a metodologia encontrada na literatura pertinente e baseada nos cálculos especificados. A apresentação do estudo é realizada pelo desenvolvimento matemático, utilizando as correlações de Palen para o lado do casco e para o interior dos tubos as correlações descritas por Gnielinski e Iqbal e Bansal (2011). O equipamento resultante teve um coeficiente global de transferência de calor de 431 W/m²·K, para uma superfície de troca térmica de 5,49 m², suficiente para realizar a troca térmica de 28,25 kW. Os resultados são comparados à bibliografia utilizada e a um trocador de calor a placas, mostrando ser esse mais compacto, embora mais frágil e com maior perda de pressão (sic).
Keywords: Engenharia mecânica; Refrigeração; Termodinâmica